A framework for sustaining lean thinking with systems thinking in Malaysian aerospace companies - Suraya Ahmad (2018)
The purpose of this study is to explore how lean thinking can be sustained with systems thinking in Malaysian aerospace companies. Literature indicated that various companies failed to achieve full lean benefit. Lean has been treated as a piecemeal and should be viewed as a system. Systems thinking is an approach that sees the organization as a system that consists of interacted elements and subsystems. The study started with investigating the status of lean, the challenges encountered by the companies when practicing lean, the extent existence of systems thinking traits and to what extent the companies exhibit a learning organization. Conceptually, this study is framed within lean principles, two approaches of systems thinking with learning organization as the foundation. This study adopted qualitative multiple case study as the methodology. Three main steps in the case study protocol were followed. The data was collected through semi-structured interviews of sixteen respondents from four different companies in the aerospace industry. Thematic analysis was conducted for every case study together with the cross-case analysis. The results of this study verified that all companies faced resistance from the employees. However, there is evidence of lack of commitment from the top management and the influence of culture in the local companies. The research also confirmed that all the respondents acquired the basic systems thinking traits and the companies exhibited some characteristics of a learning organization. A framework was developed for sustaining lean thinking with systems thinking. This framework served as the foundation for enhancing the performance of lean aerospace companies. The output of this study contributed to the realization of Malaysian aerospace industry in becoming the number one in South East Asia (SEA) for parts and components sourcing before 2030.